Siltation in Zoo Negara Lake - Md Yusoff, Fatimah; Harmin, Sharr Azni (1982)
In a study of Zoo Negara Lake, it was found that the turbidity and total residues were higher in the lake than in the upstream station where there is no effect of soil erosion. The immediate results of massive flows of erosion silt were the change of water colour and reduction in the depth of the lake. Effects of siltation such as the reduction in light penetration and aquatic organisms are discussed.